(3QSGdI aj CSHGH MOhK GdMQhas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hMOg hHYO adjS cd bGHd gOjI eMJGLkG EdjgG hdG cd WGdH JMaI aGbOkG EdjgG GdChd ai SHH MOhK GdUhJ s
(3BNQgG (B:s
(3Ch hbhY TF ajgG OaYg MJi jVWQ GdghGA Edi Cf jfVZW eYg Ke jfUQa aggfG CNJJe GdQSGdI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGOSIs
(3QSGdI Edi GdCSJGP CHh efUhQ eMeO Hf Ydi Hf YeQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B861s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdadSaI hGdefWbs